THE DOCTRINE OF THE VIRGIN BIRTH IN CHRISTIANITY FROM THE PERSPECTIVE OF COMPARATIVE RELIGION: APPROACHES AND INTERPRETATIONS - Yuri V. Sobolev (Sovremennye Issledovaniâ Socialʹnyh Problem)
The article offers an examination of the doctrine of the virgin birth in Christianity within the framework of intra-confessional discussion. Paying attention to the emphasis of the doctrine of the virgin birth in the modern Protestant tradition, the question of the place and significance of the doctrine of the virgin birth in the church tradition (Orthodox and Catholic) is introduced into the problem field of the study. Separately, the question of the possibility of the new birth in an age of “the waning of faith” is raised. The interdisciplinary approach in the study allows us to identify a number of important provisions that determine the difference and commonality in the interpretations of the two traditions: the authority of holy theological exegesis, the significance and place of the oral tradition in modern Protestant communities, the primary and secondary in the understanding of the hierophanic, the rational and mystical in the spiritual experience of the believing Christian. The works of such scholars and researchers as: M. Weber, D. Melton, M. Eliade, M. Foucault, L. Harrison, D. Bogolepov, S. Horuzhiy, I. Yablokov. An important place in the study of the issue is occupied by the holy theological heritage - the works of John Chrysostom and Simeon the New Theologian. As methods of research were used: the method of comparative religious studies, hermeneutic-textual analysis, socio-historical and cultural approaches. In the course of the work, a number of important conclusions have been drawn about the understanding and place of the doctrine of the virgin birth in Christian doctrine. The most important of which are: the significance of explicitness and understanding of the virgin birth in Protestantism; the complexity and implicitness of the Church's exegesis of the virgin birth, expressed in two main vectors of understanding of this question. These articles can be used in the research activities of philosophers-religionists on the history of Christianity. The practical value of the study lies in the possibility of incorporating the results into classes in philosophy, religious studies and theology, as well as directly in missionary activities.